Food authenticity, food safety and religious observances as likely determinants of food tourism / Debbie Ferdinand Moginon - Debbie Ferdinand Moginon (2010)
The significance of food and tourism cannot simply be ignored. What are the underlying factors within the role of food itself that can be a major draw or motivator for tourists to visit a particular destination and/or be involved in whatever food-related activities, in other words engaging in food tourism? In respond to this, the purpose of this study is to examine the role of authenticity, food safety and religious observances on the facet of food tourism as well as taking into account the varying tourists’ country of origin. In the context of this study, country of origin was specifically translated into five regions (Africa, Americas, Asia, Oceania, Europe and Middle East). The study seeks to address this by employing data in which was drawn from international tourists or visitors via self-completed questionnaire at Low Cost Carrier Terminal, Sepang and Kota Kinabalu International Airport, Sabah. The survey included a total of 166 respondents. The data was coded and analyzed by the use of SPSS version 17.0. According to the findings, both food authenticity and food safety significantly contributed to the prediction of food tourism where food authenticity had the most impact. Religious observances on the other hand were not significant in predicting food tourism. The results of this study also highlighted that country of origin did not influence the relationship between food authenticity and food tourism, nor did it influence the relationship between food safety and food tourism. There seems to be an indication of no differences found between Africa, Americas, Asia, Oceania, Europe and Middle East on the relationship between religious observances and food tourism. Nevertheless, it was also found that if each facet of food authenticity, food safety and religious observances was assessed individually among respondents, differences can be found, especially on the facet of religious observances. The results of this study offer several implications emphasizing on two major contributions, namely, theoretical and practical implications. In theoretical implications, the study basically enriched the body of literature by providing further insight on the facet of food authenticity, food safety and religious observances as well as food tourism. The findings of this study also provide some insights in assisting tourist destination and tourism suppliers as well as tourism marketers in promoting food tourism, that is taking into account and reinforcing the aspect of authenticity of food and its safety.